2020
DOI: 10.1108/ssmt-11-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution and micromechanical properties of SAC305/CNT/CU solder joint under blast wave condition

Abstract: Purpose The purpose of this paper is to investigate the effect of carbon nanotube (CNT) addition on microstructure, interfacial intermetallic compound (IMC) layer and micromechanical properties of Sn-3.0Ag-0.5Cu (SAC305)/CNT/Cu solder joint under blast wave condition. This work is an extension from the previous study of microstructural evolution and hardness properties of Sn-Ag-Cu (SAC) solder under blast wave condition. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It is known that CNT did not react with the elements in the SAC305 solder matrix to form some stable intermetallic compound. 29 However, the microstructure of SAC305 solder joint was found to have been changed due to the incorporation of CNT. From the EDX mapping, the SAC305-CNT0.04 solder matrix indicates a broad distribution area of the eutectic phase compared to the SAC305 solder.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that CNT did not react with the elements in the SAC305 solder matrix to form some stable intermetallic compound. 29 However, the microstructure of SAC305 solder joint was found to have been changed due to the incorporation of CNT. From the EDX mapping, the SAC305-CNT0.04 solder matrix indicates a broad distribution area of the eutectic phase compared to the SAC305 solder.…”
Section: Resultsmentioning
confidence: 99%
“…Both samples were ground with 240, 320, 600, 800, 1000, and 2000 grit Silicon Carbide paper with flowing water. Subsequently, diamond paste of 6, 3, and 1 micron was used to polish the surface, followed by oxide polishing for up to 60 seconds [1,2]. The solder balls' microstructure was then examined using an optical microscope and evaluated with ImageJ software.…”
Section: Characterizationmentioning
confidence: 99%
“…The performance of electronic devices depends on continuous improvement in miniaturization, application, technology, and cost. One of the most important advances that keeps electronics manufacturers constantly on their toes is the introduction of an extremely dense integrated circuit with higher reliability for various applications up to extreme conditions with finer pitch of solder joint interconnection [1][2][3][4][5]. When utilized in surface mount technology (SMT), interconnect technology such as ball grid array (BGA), offer a special advantage as they provide integrated circuit (IC) package technology, which makes devices with integrated circuits smaller, cheaper, and reduction in weight, with increased performance.…”
Section: Introductionmentioning
confidence: 99%
“…Pun et al (2016) have studied the effect of substrate surface finish, pad sizes and substrate flatness on occurrence of solder joint failure in Cu pillar solder flip chip interconnects. Ismail et al (2021) have examined the influence of carbon nanotube (CNT) addition on microstructure, interfacial intermetallic compound (IMC) layer and micromechanical properties of solder joint under blast wave condition. Their results showed that the explosive weight of microstructure is increased as the interfacial layer is increased.…”
Section: Introductionmentioning
confidence: 99%